Comparison of CMIP6 and CMIP5 simulations of precipitation in China and the East Asian summer monsoon. (27th April 2020) - Xin, Xiaoge; Wu, Tongwen; Zhang, Jie; Yao, Junchen; Fang, Yongjie
Abstract: We evaluate and compare the simulation of summer precipitation in China and the East Asian summer monsoon (EASM) by eight climate models from Phase 6 of the Coupled Model Intercomparison Project (CMIP6) and the corresponding eight previous models from CMIP5. Skill metrics are calculated to assess the climatology, interannual variation and linear trends during the time period 1961–2005. The CMIP6 multimodel ensemble (MME) is more skillful than the CMIP5 MME in the spatial correlation and standard deviation ( SD) of the climatological precipitation over Eastern China. All the CMIP6 models improve the skill scores in the climatological pattern of the EASM relative to the previous models of CMIP5, which is related to their smaller sea surface temperature (SST) biases over the Northwestern Pacific Ocean. The models with a higher capability in reproducing the climatological pattern of the EASM tend to have a better skill in simulating summer precipitation over Eastern China. Most (six of eight) of the CMIP6 models have advantages over the previous CMIP5 models in reproducing the interannual anomalous rainfall pattern over Eastern China related to the EASM. Ten of the 16 models partly reproduce the weakening trend of the EASM during 1961–2005. The high‐skill models (GISS‐E2‐H, GISS‐E2‐1‐H) that simulate a clear weakening trend in the EASM also reasonably simulate the negative correlation between the EASM and the SST over Eastern Indian and the Western Pacific Oceans (EIWP). By contrast, the two models (CESM2 and CESM2‐WACCM) that simulate a positive correlation over the EIWP both produce increasing trends in the EASM indices. This indicates the importance of climate models in simulating the relationship between the EASM and the SST over the EIWP. Among the 16 models, only 2 CMIP6 models (BCC‐CSM2‐MR and GISS‐E2‐1‐H) partly reproduce the linear trend of precipitation over Eastern China, featured by the pattern of "southern flood and northern drought." Abstract : The Phase 6 of the Coupled Model Intercomparison Project (CMIP6) models show advantages over the previous CMIP5 models in simulating the climatology and interannual pattern of East Asian summer monsoon (EASM) and precipitation over Eastern China. The models with higher capability of reproducing the climatological pattern of the EASM tend to have better skill in simulating summer precipitation over Eastern China, which is related to their smaller sea surface temperature (SST) biases over the Northwestern Pacific Ocean (NWP). The relationship between SST over Eastern Indian and the Western Pacific Ocean and the EASM is important for the simulation of linear trend of the EASM. The figure shows the scatterplot (a) between the skill scores of climatological summer 850 hPa wind skill score over East Asia and precipitation in Eastern China and (b) between skill scores of climatological summer 850 hPa wind skill score over East Asia and the SST bias over the NWP (10°–30°N, 110°–160°E) in CMIP5 and CMIP6 models.